Additional file 2 of Using light-level geolocations to monitor incubation behaviour of a cavity-nesting bird Apus apus pekinensis - Xiao Huang (223709); Yanyan Zhao (211551); Yang Liu (9563164) (2021)
Additional file 2: Table S1. The specific onset and end date of different reproduction period of six individuals of Beijing Swifts inferred from light-level geolocators.